Characterization of Dogs and Cats Diagnosed With Diseases of the Urinary System in 2019: Veterinary Hospital, Faculty of Veterinary Medicine, University of San Carlos De Guatemala (Global Journal of Medical Research, 2021)
If determined the casuistry of diseases that affect the urinary system in dogs and cats. A retrospective study was carried out at the Veterinary Hospital of the University of San Carlos de Guatemala. It was characterizing patients with diseases of the urinary system. 1,205 canine and feline medical records were evaluated in 2019. The variables breed, sex, age, pathology and geographic area were considered. The prevalence of urinary system diseases in dogs and cats in 2019 was 10.45%, 9.21% corresponding to dogs and 1.24% to cats. In both species, males had a higher frequency of urinary system disease, compared to females (dog = 58.56% and cat = 66.67%). The most common etiologies in dogs were lower urinary tract infections (24.65%), bladder urolithiasis (16.90%), and acute and chronic kidney disease (28.16%); while in cats lower urinary tract disease (100%) and kidney disease (5.26%) were the main pathologies observed. In dogs, the most affected age range was in patients older than 8 years (52.25%), while in cats it ranged from 3 to 8 years (73.34%).
Keywords: urinary system; canine; feline; prevalence